Spores of Trichoderma strains sprayed over Acanthoscelides obtectus and Phaseolus vulgaris L. beans: Effects in the biology of the bean weevil. (September 2020) - Rodríguez-González, Álvaro; Campelo, María Piedad; Lorenzana, Alicia; Mayo-Prieto, Sara; González-López, Óscar; Álvarez-García, Samuel; Gutiérrez, Santiago; Casquero, Pedro Antonio
Abstract: Acanthoscelides obtectus is an insect pest feeding on common beans Phaseolus vulgaris. Three strains of Trichoderma harzianum and one strain of Trichoderma citrinoviride were sprayed on insect adults and Phaseolus vulgaris L. beans in order to investigate the efficiency of the fungi in combating Acanthoscelides obtectus insect pest. The strains E20, T34, and T019 exhibited high virulence on adults. Spores of T34 isolate were more attractant for both sexes and showed a higher mortality rate on insects in contact with treated beans than the other strains. Treated beans showed a lower weight loss compared to the untreated ones. T019 and T008 treatments resulted in a lower weight loss of beans than the other fungal strains. Daily insect emergence was reduced in treated beans. The strain T34 accounted for the lowest daily emergence of insects. T008, T019, and E20 exhibited the capacity to repel insects, which resulted in a reduction of damaged beans as well as a lower number of holes per bean. Trichoderma strains were re-isolated from insects' cadavers extracted from treated beans. Regarding these results, T34 strain could be used in the control of A. obtectus adults due to its high lethal effect. Additionally, T008 and T019 strains, showing good results in terms of insecticidal activity, insect repellency, reduction of damaged beans and lower weight loss of beans, could also be used for the biological control of A. obtectus. Graphical abstract: Image 1 Highlights: Acanthoscelides obtectus is an insect pest that attacks Phaseolus vulgaris L . Four Trichoderma strains were evaluated against A. obtectus adults. Treated beans with Trichoderma strains showed a lower weight loss. Daily emergence was reduced in treated beans with the T34 strain. Spores of T008, T019 and E20 had the capacity to repel insects. T008 and T019 can carry out a biological control of A. obtectus .